2006
DOI: 10.1016/j.aquaculture.2006.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Composition in essential and non-essential elements of early stages of cephalopods and dietary effects on the elemental profiles of Octopus vulgaris paralarvae

Abstract: International audienceDuring the present study, we aimed at providing a first look at the elemental composition of the early stages of cephalopods as an approach to their elemental requirements in culture. Essential and non-essential elemental profiles of the European cuttlefish Sepia officinalis, the European squid Loligo vulgaris and the common octopus Octopus vulgaris laboratory hatchlings and wild juveniles were analysed. In addition, for O. vulgaris we determined elemental profiles of mature ovary, eggs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 80 publications
7
74
2
1
Order By: Relevance
“…Lacoue-Labarthe et al 2009). In the octopod Octopus vulgaris however, calcium concentration increases during the oocyte development, suggesting that this essential element could be obtained from seawater intake (Villanueva and Bustamante 2006). It has been previously demonstrated that the eggshell displays a selective permeability to dissolved trace elements, independently of their essential or non-essential character (Bustamante et al 2002, Lacoue-Labarthe et al 2008, and that changes in seawater pCO 2 conditions could affect these properties (Lacoue-Labarthe et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacoue-Labarthe et al 2009). In the octopod Octopus vulgaris however, calcium concentration increases during the oocyte development, suggesting that this essential element could be obtained from seawater intake (Villanueva and Bustamante 2006). It has been previously demonstrated that the eggshell displays a selective permeability to dissolved trace elements, independently of their essential or non-essential character (Bustamante et al 2002, Lacoue-Labarthe et al 2008, and that changes in seawater pCO 2 conditions could affect these properties (Lacoue-Labarthe et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In cephalopods, the requirements in essential elements are poorly known and only few studies have examined the elemental content of early stages (Craig and Overnell 2003, Villanueva and Bustamante 2006, Miramand et al 2006. Calcium reserves needed for metabolic processes could be contained in the rich yolk of the cuttlefish egg (Boletzky 1974(Boletzky , 1989e.g.…”
Section: Discussionmentioning
confidence: 99%
“…High P invertebrate predators may be much more vulnerable to the effects of P-depletion in herbivorous zooplankton. Examples might be early life stages of molluscs, such as squids and cuttlefish (VILLANUEVA and BUSTAMANTE, 2006), which have very high growth rates. Experiments with young Sepia officinalis (MELZNER et al, 2005) and Loligo opalescens (VIDAL et al, 2006) paralarvae have shown that growth rates are tightly coupled to RNA : DNA ratios and P-demand (GILLOOLY et al, 2005), and that RNA concentrations are exceptionally high in fast growing individuals.…”
Section: Relevance and Implicationsmentioning
confidence: 99%
“…Useful information was obtained about the nutritional requirements of paralarvae by the comparison of the chemical profiles of mature ovaries, eggs at different developmental stages, fresh hatchlings and wild juveniles with the chemical profiles of paralarvae cultured for one month with different live natural prey and with those of the prey administered Villanueva, 2000, 2003;Villanueva et al, 2002Villanueva et al, , 2004Villanueva et al, , 2009Villanueva and Bustamante, 2006). Special attention was paid to polyunsaturated fatty acids (PUFA), especially docosahexaenoic (DHA), DHA/ eicosapentaenoic (EPA) ratio, phospholipids, cholesterol, to some essential amino acids (lysine, leucine and arginine representing about 50% of the total essential amino acids of paralarvae), mineral (copper) and vitamins (Vitamin A, but especially Vitamin E; Villanueva et al, 2009).…”
Section: Larval Rearing and Feedingmentioning
confidence: 99%